Global systematic map of research on bats in agricultural systems - Xavier, Bruna Silva; Rainho, Ana; Santos, Ana M. C.; Vieira, Marcus Vinícius; Carvalho, William Douglas (Frontiers in Ecology and Evolution, 2023)
The conversion of natural habitats to commercial plantationsagricultural systems is one of the main global threats to bats. We followed a review protocol to develop a systematic map to identify publication trends and research gaps in studying of bats and agricultural systemscommercial plantations. We reviewed 309 studies published between 1990 and 2021 that sampled bats in agricultural systemscommercial plantations or evaluated the effect of these plantationssystems on these animals. We found that most studies were conducted in the Palearctic and Neotropical regions (55.3%) and forest biomes (66.0%), highlighting the need for studies in the Afrotropic and Indo-Malaysia regions and predominantly non-forested biomes. Non-forest plantationsGrassland-cropland systems (4950.2%) and forest plantations that do not require cutting during the extraction of their products (47.96.0%) were more studied than forest plantations that require cutting (2019.7%). Additionally, acoustic recordings (41.1%) and mist nets (34.3%) were the primary sampling methods, with few studies combining these methods (7.1%). So, future studies should use a combination of these methods, as well as other methods as telemetry. Most studies were conducted on a local scale (77.7%). The number of landscape-scale studies was smaller (34.3%) and concentrated in the Palearctic region (39.6% of landscape scale studies). Most studies assessed how agricultural systemsplantations affect biodiversity (62.1%). However, the phylogenetic and functional dimensions and β-diversity were little explored, with 2.5% and 23.3% of the biodiversity studies, respectively. Thus, it is necessary a better understand of the impact of agricultural systems plantations on a set of multiple biodiversity descriptors and others biological descriptors. Of the proposed mitigation measures, the most cited was including natural/semi-natural/potential bat habitats in cultivated planted landscapes (59.5%). Filling these knowledge gaps is necessary to understand the factors influencing bat survival in plantedcultivated landscapes. This is the only way to develop management and conservation strategies in these landscapes.